DDIT3 antagonizes innate immune response to promote bovine alphaherpesvirus 1 replication via the DDIT3-SQSTM1-STING pathway. Issue 1 (31st December 2022) - Wang, Song; Ma, Xiaomei; Guo, Jin; Li, Fangxu; Chen, Tianhua; Ma, Wenqing; He, Chengqiang; Wang, Hongmei; He, Hongbin
ABSTRACT: DNA damage-inducible transcript 3 (DDIT3), a transcription factor, is typically involved in virus replication control. We are the first to report that DDIT3 promotes the replication of bovine viral diarrhea virus, an RNA virus, by inhibiting innate immunity. However, whether the DDIT3 gene participates in DNA virus replication by regulating innate immunity remains unclear. This study reported that DDIT3 suppressed the innate immune response caused by DNA viruses to promote bovine herpesvirus 1 (BoHV-1) replication. After BoHV-1 infection of Madin-Darby bovine kidney (MDBK) cells, upregulated expression of DDIT3 induced SQSTM1-mediated autophagy and promoted STING degradation. Overexpression of the SQSTM1 protein effectively reduced STING protein levels, whereas SQSTM1 knockdown increased STING protein levels. Coimmunoprecipitation experiments and confocal laser scanning microscopy revealed that the SQSTM1 protein interacts with and colocalizes with STING. Knockdown of SQSTM1 expression in DDIT3-overexpressing cell lines restored STING protein levels. Moreover, a dual-luciferase reporter assay revealed that DDIT3 directly binds to the bovine SQSTM1 promoter and induces SQSTM1 transcription. Overexpression of SQSTM1 promoted BoHV-1 replication by inhibiting IFN-β and IFN-stimulated genes (ISGs) production; silencing of SQSTM1 promoted the expression of IFN-β and ISGs to inhibit BoHV-1 replication. In conclusion, DDIT3 targets STING via SQSTM1-mediated autophagy to promote BoHV-1 replication. These results suggest a novel mechanism by which DDIT3 regulates DNA virus replication by targeting innate immunity. DDIT3 antagonizes the innate immune response to promote bovine alphaherpesvirus 1 replication via the DDIT3-SQSTM1-STING pathway.